2017
DOI: 10.1097/sla.0000000000001694
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital Surgical Delay Does Not Increase the Risk for Perforated Appendicitis in Children

Abstract: In-hospital delay of acute appendectomy in children was not associated with an increased rate of histopathologic perforation. Timing of surgery was not an independent risk factor for postoperative complications. The results were not dependent on the magnitude of the surgical delay. The findings are analogous with previous findings in adults and may aid the utilization of available hospital- and operative resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 23 publications
3
32
0
1
Order By: Relevance
“…Two‐thirds of the studies were published in or after 2010. Seven studies analysed only children under the age of 18 years; the other 38 studies analysed adults alone or children and adults combined.…”
Section: Resultsmentioning
confidence: 99%
“…Two‐thirds of the studies were published in or after 2010. Seven studies analysed only children under the age of 18 years; the other 38 studies analysed adults alone or children and adults combined.…”
Section: Resultsmentioning
confidence: 99%
“…26 Our data showed that patients with appendiceal perforation required a significantly longer hospitalization period and a greater number of radiographic imaging procedures during hospitalization. One of the interesting findings of this study is the fact that delayed appendectomy was associated with a significant increase in perforation rates, whereas no such negative effect was observed in the rate of SSI.…”
Section: Discussionmentioning
confidence: 86%
“…The mean age of patients was 33.1±18 and, 41.8±20.7 years 26.4% of the non-perforation group patients and 37.7% of the perforation group patients (p=0.0075). Also, the mean hospital visitto-operation time was 9.2±5.6, 11±6.3 hours, respectively in non-perforation group and perforation group (p<0.0001).…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations